Legal Review Regarding Appointment of Ambassador in Indonesia Based on Gender Equality - Warasli Tafonao; Setiaman Gea; Zetria Erma (IHSA Institute, 2023)
The purpose of conducting this research is to find out how the position of the President in Indonesia is and the mechanism for appointing Ambassadors of the Republic of Indonesia, where the majority still appoint men only. For this reason, it is appropriate for women's groups so that gender equality occurs. This type of research is normative with a statutory and conceptual approach. While the specification of the research is analytical descriptive, namely explaining the problem according to the research title. Primary data is in the form of the 1945 Constitution and secondary material is in the form of books, journals, electronic news, laws and regulations and legal expert opinions as well as writings related to research titles. The President in appointing the Indonesian Ambassador must pay attention to the considerations of the People's Representative Council. The position of the President in Indonesia and the mechanism for appointing the Ambassador of the Republic of Indonesia based on gender equality with the consideration of the DPR is very necessary in the interest of cooperation between countries. Therefore, it is suggested that the government be more assertive and clarify the provisions governing the position and accountability mechanism of a president as the head of state in appointing an Indonesian Ambassador in accordance with the system of government adopted by the Indonesian state which provides equal opportunities to all prospective ambassadors, both male and female, serve in any area regardless of the conditions. And it is necessary to hold a procedure for appointing an Indonesian Ambassador to ensure transparency over the prospective Ambassadors who are placed to have sufficient capacity and capability to realize the national interests of all Indonesian people regardless of gender while on duty and work regardless of the territory occupied.